A Base Nacional Cumum Curricular: uma análise com ênfase no ensino de Ciências do 6° ao 9° ano do ensino fundamental - SOUZA, Maria Adlayne Gomes de (2022)
On December 22, 2017, the curricular common national base (CCNB), was published as an official normative document that will serve as a reference for the formulation of Basic Education curriculum in federal, state, municipal and Federal District education systems. Studying this document is of fundamental importance for teachers and for the graduating, because such document has been published by the Ministry of Education promising to provoke a great change in Brazilian education with the objective of updating it to, in fact, to ensure the essential learning for all students of Basic Education throughout the Country. In view of this, this Course Conclusion Paper was developed with the purpose of answering the following question: What changes in Brazilian education and in the performance of the science teacher, due to the influence of the implementation of the National Curricular Common Base? To answer this question, a theoretical research was developed with a qualitative approach, classified according to the objectives in a descriptive and classified research regarding procedures in documentary research, with the following general objective: to present an analysis on the text of the National Curricular Common Base, especially the part that deals with the teaching of Sciences from the 6th to the 9th year of Elementary Education. Being the object of study of this research an official document, then for the data collection was used the technique of content analysis on the text of this document. The results of this analysis have shown that BNCC will bring about two major changes in curricula - study of school contents for the development of skills and competences and a significant change in the didactic sequence of elementary school science teaching - and this will probably cause major changes in the way the teacher works, including requiring them to be continuously trained to obtain an update consistent with the current demands that the BNCC brings to their professional practice and social function.